Sustainability economics - Zhang, Lin (Springer, 2025)
This book is an essential guide to understanding and tackling the complex challenges of sustainable development.It provides a thorough analysis of economic principles and their application to pressing sustainability issues. Covering everything from foundational theories and energy dynamics to environmental impacts and social justice, it provides actionable insights into how businesses, policymakers, and communities can drive sustainable progress. With a focus on real-world applications, it explores the latest in energy efficiency, climate policy, and green finance, making it a critical resource for students, professionals, and anyone passionate about creating a more sustainable future. Whether you're looking to deepen your understanding of sustainability economics or seeking practical strategies for implementing sustainable practices, this book offers a rich blend of theory, analysis, and practical guidance.
Keywords: Environmental economics.; Sustainable development.; elektronické knihy; electronic books